Comparación morfológica y distribución geográfica de las especies Tabellaria fenestrata y Tabellaria flocculosa (Bacillariophyceae) en sistemas lóticos y lénticos de Colombia. (2017)
ABSTRACT: This study was developed within the framework of a project conducted with the aim of analyzing the geographical distribution of diatoms in Colombia. This project was based on analyses of information on lotic systems located in the biogeographic regions of the Andes, Caribbean, Orinoquía and Pacific. During the research, periphyton samples were collected at 18 sampling sites. Current flow rate, temperature, pH, conductivity, dissolved oxygen and elevation were measured in each sampling site. We report the presence of two taxa belonging to the genus Tabellaria: T. fenestrata and T. flocculosa, which are morphologically similar and, therefore, have been frequently misidentified. Specimens of both taxa were observed and described with light microscopy and scanning electron microscopy. We also analyzed the geographical distribution of these taxa in the country. We conclude that T. flocculosa has a broad geographical distribution in Colombia and few ecological restrictions to colonize and settle in aquatic systems, while T. fenestrata has a more restricted distribution.